Assessing Structural Performance: A Combined Qualitative and Quantitative Approaches Using Multi-Criteria Decision-Making Method - Sara Sadeghi
The study introduces a framework for evaluating architectural structures by integrating qualitative and quantitative criteria. The research begins with a literature review to identify key factors influencing structural performance. Experts refined and categorized these factors using the Delphi method. The DEMATEL method was applied to evaluate the interconnections and significance of the criteria, showing that mechanical and environmental factors were the most impactful, with mechanical aspects assigned the highest weight of 0.376. Aesthetic considerations were nearly as significant as environmental factors, highlighting their importance in contemporary architectural evaluation. The AHP method was used to determine the final weights, with all inconsistency rates below 0.1, indicating reliable results. The study's findings underscore the need for a balanced approach in architectural design, integrating qualitative factors alongside traditional quantitative measures. This comprehensive framework offers a more holistic evaluation of structural performance, advancing both academic research and practical application in architecture. The research highlights the importance of considering aesthetic and environmental aspects in addition to mechanical and economic factors, contributing to more sustainable and visually appealing architectural designs.